The role of disclosure in the business model report in improving the quality of financial reports - Abdulrahman Saeed Ali *; Hammeed Jassam Hommadi (مجلة الدراسات الاقتصادية والادارية)
In the field of accounting, the business model report has received great academic and applied attention, especially in recent years. This study aims to enhance the quality of companies' financial reports through disclosure within the business model report. To achieve this goal, a questionnaire was designed and distributed to test the identification of aspects of enhancing the quality of companies' financial reports in the business model report. A questionnaire was distributed to a research sample of 70 people from different categories. The results were analyzed and discussed, as there were different percentages of agreement regarding the paragraphs that were identified as aspects of enhancing the quality of financial reports through disclosure within the business model report. The study concluded that using the business model report to disclose important parameters provides aspects that enhance the quality of companies' financial reports. At the same time, there is still a deficiency in establishing the theoretical, organizational and legal basis for the information content of the business model report, and that there is a deficiency on the part of management in enhancing the business model report with more information and drawing the attention of decision-makers to its importance.